CULTURAL DIVERSITY IN CLASSES AND WORKPLACES: THE COMMUNICATION CHALLENGES - Pieniz, Mônica Bertholdo (Animus. Revista Interamericana de Comunicação Midiática, 2020)
Dr. Peruvemba S Jaya is an Associate Professor in the Department of Communication, Faculty of Arts, at the University of Ottawa. Prior to that, she has been in teaching in faculties of business in the USA and Canada. She has a PhD in Business Administration (Organizational Behaviour and Organizational Studies) from the University of Rhode Island, USA, MA in Sociology from the Delhi School of Economics, University of Delhi, India and BA (Hons) in Sociology from the University of Delhi, India. Her research interests include the areas of gender diversity and multiculturalism in the workplace, immigration and gender, immigrant women, South Asian immigrant women’s experience, immigrants’ issues, interpersonal communication, identity formation and construction processes, postcolonial theory, and intercultural communication. She is also interested in ethnic media and qualitative research methodologies. She is affiliated with the Institute of Women’s Studies, University of Ottawa as well as Affiliate Faculty in the interdisciplinary E Business and Technology PhD Program. She is a member of the Organizational Communication Research Group of the University of Ottawa, Department of Communication. She is currently the Regional Representative of Research Committee 32: Women in Society of the International Sociological Association and a Member of the Board of the Canadian Communication Association.